2015
DOI: 10.3109/14767058.2015.1114082
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acids composition of human milk fed to small for gestational age infants

Abstract: Fatty acid composition of human milk is not affected by whether or not the infant was fetal growth restricted. We suggest that mothers of SGA infants may be reassured about the fat quality of their milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…A high birth weight (BW) has been correlated with an increase in HM protein and fat content, while the levels of other nutritional components such as carbohydrates, seem not to be related to this factor. Armoni et al [ 139 ] and Lubetzky et al [ 140 ] did not detect significant differences in lipids and FAs in IUGR mothers’ HC. In a recent work published in 2017, an increased concentration of FAs (lauric, tridecanoic and iso-palmitic acids) were reported in HC from mothers delivering neonates with a BW lower than the 20th centile [ 128 , 139 , 140 ].…”
Section: Metabolomicsmentioning
confidence: 99%
“…A high birth weight (BW) has been correlated with an increase in HM protein and fat content, while the levels of other nutritional components such as carbohydrates, seem not to be related to this factor. Armoni et al [ 139 ] and Lubetzky et al [ 140 ] did not detect significant differences in lipids and FAs in IUGR mothers’ HC. In a recent work published in 2017, an increased concentration of FAs (lauric, tridecanoic and iso-palmitic acids) were reported in HC from mothers delivering neonates with a BW lower than the 20th centile [ 128 , 139 , 140 ].…”
Section: Metabolomicsmentioning
confidence: 99%
“…Interestingly, the macronutrient milk composition differed considerably from reference ranges for term breastfed infants in this SGA case, despite other studies failing to show differences [11, 1416]. This is likely due to a combination of sampling limitations that exist in previous literature.…”
Section: Discussionmentioning
confidence: 56%
“…Animal studies have reported that infant growth restriction results in compromised maternal quantity and quality of milk [13]. This is in contrast to the few human studies that have reported no change in milk composition in cases of growth restriction [1416]. These studies, however, used inappropriate sampling methods for fat analysis, collecting samples from one time point in the first 28 days post-partum, and did not consider the daily or monthly variation of fat [11, 17].…”
Section: Introductionmentioning
confidence: 99%
“… 20 Another study conducted with 60 puerperal women found no effect of fetal growth on the composition of milk fatty acids during the three phases of lactation, when controlled for gestational age. 21 …”
Section: Discussionmentioning
confidence: 99%